(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. La riforma del Terzo settore - 2. Enti ecclesiastici e riforma del Terzo settore - 3. Le condizioni per l’applicazione del regime del Terzo settore agli enti ecclesiastici - 3.1. Il regolamento - 3.2. Il patrimonio destinato - 3.3. La tenuta di scritture contabili separate - 4. Le possibili soluzioni organizzative - 4.1. Il “ramo” dell’ente ecclesiastico - 4.2. Il “gruppo” dell’ente ecclesiastico - 5. Una rete associativa per gli enti del Terzo settore ecclesiastici? The reform of non-profit organizations and Church bodies: a cost, a risk or an opportunity? ABSTRACT: While many institutional activities of Church bodies fall within the scope of the recent reform of Italian law on non-profit organizations ("NPOs"), the specific features of Church bodies prevent from a straightforward application of the new regime. Therefore, the Code for the Third Sector and the Act on Social Enterprises allow Church bodies to access the tax exemptions and the other benefits provided to NPOs as far as they comply with a set of conditions aimed at bridging the differences between Church bodies and secular NPOs. The paper (1) discusses in details these conditions, (2) offers a critical evaluation of costs, risks, and opportunities related to the new regime, and (3) suggests possible organizational structures to comply with the current system.